Continuous terbutaline infusion in severe asthma in adults: a retrospective study of long-term efficacy and safety. (December 2014) - Mansur, Adel H.; Afridi, Lisa; Sullivan, Julie; Ayres, Jon G.; Wilson, Duncan
Abstract Background: Long-term subcutaneous or intravenous infusion of terbutaline has been used to stabilize asthma in patients enduring frequent hospital admissions due to severe asthma despite maximum therapy. However, this treatment is not supported by significant body of evidence. Aim: To study long-term efficacy and safety of using continuous infusions of terbutaline in unstable severe asthma. Methods: The available medical records of all patients received terbutaline infusions at a severe asthma unit between 1982 and 2008 were retrospectively studied. We retrieved data on treatment indication, asthma subtype, patient demographics, pre-treatment terbutaline trial outcome, duration of treatment, effect on lung function, hospital admissions, oral corticosteroids (OCSs) requirement, safety and side effects. Results: Forty-two patients with adequate medical information were studied (31 females, mean age 43.6 years, 88% had type 1 brittle asthma and 12% had other severe asthma). This group of patients had a mean body mass index of 30.8 kg/m2, mean oral prednisolone or equivalent of 26.6 mg and mean predicted FEV1 of 66.8%. The mean treatment duration was 86.7 months (range 7–216). Long-term continuous terbutaline infusion significantly reduced hospital admissions (mean pre-treatment = 6.7 (95% CI 0.96–12.4) per annum, and mean annualized on-treatment admission = 3.3 (95% CI 0.63–6.9, p = 0.045). We observed overall reduction in OCSs use in 59% of patients with available data, but there was no significant change in lung function. Side effects related to terbutaline or the method of its infusion were common and some were serious especially when central venous access device were used. Conclusion: Continuous terbutaline infusion could be a treatment option for severe unstable asthma and may reduce hospital admissions. However, the treatment was associated with significant side effects and its use should be limited to centers possessing necessary expertise.